The novel mitochondrial tRNA(Asn) gene mutation m.5709T>C produces ophthalmoparesis and respiratory impairment - Ronchi, Dario (Nature Publishing Group, 2012)
Although mutations in mitochondrial tRNAs constitute the most common mtDNA defect, the presence of pathological variants in mitochondrial tRNA(Asn) is extremely rare. We were able to identify a novel mtDNA tRNA(Asn) gene pathogenic mutation associated with a myopathic phenotype and a previously unreported respiratory impairment. Our proband is an adult woman with ophthalmoparesis and respiratory impairment. Her muscle biopsy presented several cytochrome c oxidase-negative (COX−) fibres and signs of mitochondrial proliferation (ragged red fibres). Sequence analysis of the muscle-derived mtDNA revealed an m.5709T>C substitution, affecting mitochondrial tRNA(Asn) gene. Restriction-fragment length polymorphism analysis of the mutation in isolated muscle fibres showed that a threshold of at least 91.9% mutated mtDNA results in the COX deficiency phenotype. The new phenotype further increases the clinical spectrum of mitochondrial diseases caused by mutations in the tRNA(Asn) gene.